Determining the minimal important differences in the International Prostate Symptom Score and Overactive Bladder Questionnaire: results from an observational cohort study in Dutch primary care - Harma Johanna Alma; Henk van der Worp; Martijn G Steffens; Marco H Blanker; Tahira Sakina Devji; Marjan Roelofs (BMJ Open, 2019)
Objectives To determine the minimal important difference (MID) of the International Prostate Symptom Score (IPSS) and the Overactive Bladder Questionnaire short form (OAB-q SF) assessed in primary care among patients treated for lower urinary tract symptoms (LUTS).Design Single-arm, open-label observational cohort study with a 6-week follow-up.Setting Twenty-two pharmacies in the Netherlands.Participants We enrolled Dutch men with uncomplicated LUTS who received a new alpha-blocker prescription from their general practitioner or urologist.Primary and secondary outcomes The IPSS and OAB-q SF were completed before and after 6 weeks of therapy. At 6 weeks, men also completed the Patient Global Impression of Improvement (PGI-I). The mean change scores of the IPSS and OAB-q SF were calculated for each PGI-I outcome category, with the category ‘a little better’ used to determine the MID. The SE of measurement (SEM) was calculated for each questionnaire.Results In total, 165 men completed follow-up. The MID was 5.2 points (95% CI 3.9 to 6.4; SEM 3.6) for the IPSS and 11.0 points (95% CI 7.1 to 14.9; SEM 9.7) for the OAB-q SF. For both questionnaires, CIs showed an overlap with the no-change categories. However, the MID for the IPSS was higher in men with severe baseline symptoms (7.1; 95% CI 5.3 to 9.0) than in men with moderate baseline symptoms (3.2; 95% CI 1.7 to 4.8).Conclusion In this study, the MID for the IPSS was considerably higher than the MID of 3.1 reported in the only other study on this topic, but may be due to methodological differences. Interpretation of the MID for the OAB-q SF is hampered by the overlap with the SEM. Future studies are needed to confirm our results because correlations between the PGI-I and symptom questionnaires were suboptimal.